High-sensitivity C-reactive protein and mean platelet volume as predictive values after percutaneous coronary intervention for long-term clinical outcomes: a comparable and additive study. Issue 1 (January 2016) - Moon, Ae Ran; Choi, Dong-Hyun; Jahng, Su-Young; Kim, Bo-Bae; Seo, Hong-Joo; Kim, Sang Hun; Ryu, Sang-Wan; Song, Heesang; Kim, Tae-Hyoung
Abstract : This study was designed to establish the relationship of high-sensitivity C-reactive protein (hsCRP) and mean platelet volume (MPV) with the development of adverse outcomes after percutaneous coronary intervention (PCI). hsCRP levels and MPV were analysed in 372 patients who underwent PCI, with the primary endpoint as major adverse cardiac and cerebrovascular events (MACCE): a composite of cardiac death, myocardial infarction (MI), target vessel revascularization (TVR), ischemic stroke and stent thrombosis. During the follow-up period (mean, 25.8 months), there were 21 cardiac deaths, 10 MIs including four stent thrombosis events, seven ischemic strokes and 29 TVRs. The hsCRP cut-off level was set at 0.31 mg/dl using the receiver operating characteristic curve to differentiate between the groups with and without MACCE. The MPV cut-off level was set at 8.00 fl by the receiver operating characteristic curve to differentiate between the groups with and without MACCE. A Kaplan–Meier analysis revealed that the high hsCRP group (≥0.31 mg/dl) had a significantly higher cardiac death and MACCE rate than the low hsCRP group (<0.31 mg/dl), and the high MPV group (>8.00 fl) had a significantly higher cardiac death and MACCE rate than the low MPV group (⩽8.00 fl). Furthermore, the high hsCRP and MPV groups were significantly associated with an increased risk of MACCE. These results show that hsCRP and MPV are predictive markers after PCI for MACCE; they are also additively associated with a higher risk of MACCE.